Pākistānī rājanītira biśa bachara - Hosena, Taphājjala, 1911-1969 (Bāṃlādeśa Buksa Iṇṭāranyāśanāla, 1981)
Twenty years of government and politics in Pakistan, since 1947; reminiscences of a Bengali journalist, with editorial introduction on the life and work of the author.